Endogenous CRISPR-Cas System-Based Genome Editing and Antimicrobials: Review and Prospects - Li, Yingjun; Peng, Nan (Frontiers in Microbiology, 2019)
CRISPR-Cas systems adapt ‘memories’ via spacers from viruses and plasmids to develop adaptive immunity against mobile genetic elements. Mature CRISPR RNAs guide CRISPR-associated nucleases to site-specifically cleave target DNA or RNA, providing an efficient genome engineering tool for organisms of all three kingdoms. Cas9, Cas12 and Cas13 are single proteins with multiple domains that are the most widely used CRISPR nucleases of the Class 2 system. However, these CRISPR endonucleases are large in size, leading to difficulty for manipulation and toxicity for cells. Most archaeal genomes and half of the bacterial genomes encode different types of CRISPR-Cas systems. Therefore, developing endogenous CRISPR-Cas systems-based genome editing will simplify manipulations and increase editing efficiency in prokaryotic cells. Here, we review the current applications and discuss the prospects of using endogenous CRISPR nucleases for genome engineering and CRISPR-based antimicrobials.